THE MOTIVATIONS FOR THE EMERGENCE OF CROWD TRANSLATION PHENOMENA - Tavares, Célia (2017)
This intends to reflect upon the socialization process that translation has been experiencing, and that is characterized by a large number of completely different individuals, volunteers, and with possibly no formal competencies in languages, that are formally translating. These individuals are having an important role in the translation activity, namely for web environments, and are allowing the emergence of a new mass translation model called crowd translation. This translation model emerges within a context where mass phenomenon are having an impact in several areas of society, impacting translation as well. Thus, in order to better understand crowd translation, this paper will address the effects of collective approaches that can be seen in virtual communities of practice and crowdsourcing, bearing in mind that the wisdom of the crowds is having an enormous influence in the development of these phenomenon. Therefore, the motivations that may lead to the proliferations of crowd translation, essentially in social networks, will be addressed, since they are one of the major promoters of this model, allowing individuals with no competencies in languages to perform such activities.